Obese patients lose weight independently of nutritional follow-up after bariatric surgery - Tess,Beatriz Helena (2015)
Summary Objective: to examine the association between preoperative body weight, adherence to postsurgical nutritional follow-up, length of postoperative period, and weight loss during the first 18 months among adults who have undergone bariatric surgery. Methods: a retrospective cohort study was conducted on 241 consecutive patients who underwent open Roux-en-Y gastric bypass (RYGBP) from January 2006 to December 2008, in a teaching hospital in São Paulo (Brazil). Data were collected through hospital records review and the variables analyzed included sex, age, immediate preoperative weight, adherence to postsurgical nutritional visits and length of postoperative period. Proportional body weight reductions during the 18-month follow-up period were examined using generalized estimating equations. Results: 81% (n=195) of participants were female, with overall mean age of 44.4 ± 11.6 years, mean preoperative weight of 123.1± 21.2 kg and mean preoperative body mass index of 47.2± 6.2 kg/m2. The overall adherence to postoperative follow- up schedule was 51% (95%CI: 44.5-57.5%). Preoperative body weight and adherence were not associated with proportional weight reduction (Wald’s test p > 0.18). Weight loss leveled off at the end of the 18-month follow-up period for both compliant and non-compliant patients (Wald’s test p = 0.00). Conclusions: our study showed that weight loss occurred steadily over the first 18 months after RYGBP, leveling off at around 40% weight reduction. It was associated with neither presurgical weight, nor nutritional follow-up and it may be primarily dependent on the surgical body alterations themselves. This finding may have implications for intervention strategies aimed at motivating patients to comply with early postsurgical and life-long follow-up.